Analisis Karakteristik Kualitas Layanan dan Kepuasan Pelanggan SPBU 74.921.05 dan SPBU 74.921.08 yang Berada Di Kota Sungguminasa - Zain, Zandy Pratama (Universitas Islam Negeri Alauddin Makassar, Indonesia, 2020)
The purpose of this study is to determine the differences between two gas stations that operate close to each other and within same traffic lane which be a reference to which gas station has a competitive advantage. The variables used in this study are service quality consist of tangibility, reliability, responsiveness, assurance, and empathy as well as customer satisfaction and were analyzed using index analysis and comparison of business characteristics. Researchers used a sample of 114 people and was carried out for 4 months. From this study, it was concluded that gas station customers felt that Gas Station 74,921.08 was superior in terms of Tangibility, Responsiveness, Empathy, and Customer Satisfaction. Then the gas station 74.921.05 excelled in terms of Reliability.